Sarcolemmal localisation of Na+/H+ exchange and Na+-HCO3- co-transport influences the spatial regulation of intracellular pH in rat ventricular myocytes. - Garciarena, C; Ma, Y; Swietach, P; Huc, L; Vaughan-Jones, R (Wiley, 2013)
Membrane acid extrusion by Na(+)/H(+) exchange (NHE1) and Na(+)-HCO3(-) co-transport (NBC) is essential for maintaining a low cytoplasmic [H(+)] (∼60 nm, equivalent to an intracellular pH (pHi) of 7.2). This protects myocardial function from the high chemical reactivity of H(+) ions, universal end-products of metabolism. We show here that, in rat ventricular myocytes, fluorescent antibodies map the NBC isoforms NBCe1 and NBCn1 to lateral sarcolemma, intercalated discs and transverse tubules (t-tubules), while NHE1 is absent from t-tubules. This unexpected difference matches functional measurements of pHi regulation (using AM-loaded SNARF-1, a pH fluorophore). Thus, myocyte detubulation (by transient exposure to 1.5 m formamide) reduces global acid extrusion on NBC by 40%, without affecting NHE1. Similarly, confocal pHi imaging reveals that NBC stimulation induces spatially uniform pHi recovery from acidosis, whereas NHE1 stimulation induces pHi non-uniformity during recovery (of ∼0.1 units, for 2-3 min), particularly at the ends of the cell where intercalated discs are commonly located, and where NHE1 immunostaining is prominent. Mathematical modelling shows that this induction of local pHi microdomains is favoured by low cytoplasmic H(+) mobility and long H(+) diffusion distances, particularly to surface NHE1 transporters mediating high membrane flux. Our results provide the first evidence for a spatial localisation of [H(+)]i regulation in ventricular myocytes, suggesting that, by guarding pHi, NHE1 preferentially protects gap junctional communication at intercalated discs, while NBC locally protects t-tubular excitation-contraction coupling.